2007
DOI: 10.1016/j.cardiores.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-mediated oxidative stress and inflammation mediate the age-dependent cardiomyopathy in ACE2 null mice

Abstract: Our findings demonstrate that the age-dependent cardiomyopathy in ACE2 null mice is related to increased Ang II-mediated oxidative stress and neutrophilic infiltration via AT1 receptors. Our combination of genetic and pharmacological approaches defines a critical role of ACE2 in the suppression of Ang II-mediated heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(204 citation statements)
references
References 50 publications
9
182
1
Order By: Relevance
“…In this study, local renal RAS was found to be highly activated, as manifested by the increased ACE expression and Ang II level and decreased ACE2 expression and Ang-(1-7) level in the cortex. As the key peptide of the RAS, Ang II exerts a variety of effects via its type 1 receptor, including vasoconstriction, sodium retention, cell proliferation and apoptosis, proinflammation and oxidative stress (30). Our study confirmed that Ang II promoted cell proliferation and enhanced reactive oxygen species production in cultured GMCs.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, local renal RAS was found to be highly activated, as manifested by the increased ACE expression and Ang II level and decreased ACE2 expression and Ang-(1-7) level in the cortex. As the key peptide of the RAS, Ang II exerts a variety of effects via its type 1 receptor, including vasoconstriction, sodium retention, cell proliferation and apoptosis, proinflammation and oxidative stress (30). Our study confirmed that Ang II promoted cell proliferation and enhanced reactive oxygen species production in cultured GMCs.…”
Section: Discussionsupporting
confidence: 79%
“…24,25,33 In contrast, ACE2 deficiency causes a marked increase in oxidative stress, which has been attributed to the diminished generation of Ang (1-7) by ACE2 deficiency as a counter regulatory mechanism to Ang II. 45 In addition, cardiac overexpression of Ang(1-7) improved Ang II-dependent cardiac hyper trophy by reducing p38 MAPK activity. 46 Therefore, we hypothesized that other mechanisms, independent from NO, might contribute to the attenuated pressor response to Ang II seen in Ang(1-7)-treated apoE(−/−) mice.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] Lending support to the role of various RAS components in oxidative injury predisposing to aging are findings that ACE2 null mice are more sensitive to Ang II-mediated oxidative stress and inflammation than wild-type littermates. 44 Moreover, overexpression of ACE2 in the central nervous system reduces oxidative stress and improves autonomic function in mice. 45 A life-prolonging effect of AT 1 receptor blockade has been proposed by a study using mice with targeted disruption of the gene encoding the AT 1A receptor (AT 1A −/− ).…”
Section: Oxygen Free Radicals Are Crucial Molecules Involved In Mitocmentioning
confidence: 99%